Editorial for the Thematic Series in Agriculture & Food Security: Climate-Smart Agriculture Technologies in West Africa: learning from the ground AR4D experiences - Bayala, Jules; Zougmoré, Robert B.; Dayamba, Sidzabda Djibril; Olivier, Alain (Springer, 2017)
Tis Tematic Series on “Climate-Smart Agriculture Technologies in West Africa: learning from the ground AR4D experiences” contains seven papers presented by researchers from four West African countries based on participatory action research conducted since 2012 in the region. Tese research activities were funded by the CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS) through a project titled “Developing community-based climate-smart agriculture through participatory action research in CCAFS benchmark sites in West Africa” (see [1]). Tis research action under the scientifc lead of the World Agroforestry Centre (ICRAF) aimed to test and validate, in partnership with rural communities and other stakeholders, scalable climate-smart village models for agricultural development that integrate a range of innovative agricultural risk management strategies.